Diabetic foot examination: findings of a screening survey performed in Jordan - Abu-Qamar, Ma'en (John Wiley & Sons, 2012)
Despite the alarming prevalence of diabetes in Jordan, there is insufficient information on foot manifestations of diabetes. Periodic screening is recommended for the prevention of diabetes-related foot complications so that foot changes can be identified in the initial stages and appropriate treatment provided in a timely manner. The purpose of the current study was two-fold: first, to report the findings of an opportunistic foot screening survey for 1072 people with diabetes recruited from nine health care facilities in Jordan; and, second, to identify whether or not they undergo periodic screening. Descriptive statistics were used to analyse data collected by trained research assistants using an ethically approved standardised protocol covering three main aspects of foot examination (dermatological inspection, and vascular and neurological assessment) with demographic data plus information on diabetic foot care. The protocol also guided the research assistant to appraise height, weight, blood pressure and blood glucose levels. The study participants were almost equally distributed in terms of gender (males: 50.9%).More than half of participants were aged between 41 and 60 years; 58.1% of the study population had diabetes of more than five years’ duration, and most of them had type 2 diabetes. Poor protective sensation was found in the feet of one-fifth of the study population, and a similar proportion was documented for foot deformities. The participants were sorted into four categories of risk for foot ulceration, ranging from risk category 0 to risk category 3. A quarter of the study population were located within risk category 3, and nearly 66% were classified into risk category 0.In conclusion, Jordanians with diabetes possess several risk factors for diabetic foot ulceration. These risk factors coexist with a lack of adherence to periodic foot screening. Efforts should be made to incorporate periodic foot screening within the context of routine care provided to individuals with diabetes.